Studying the Effect of Stand Characteristics on Plant Species Diversity in the Median Part of Natural Pinus brutia Ten. (Brutia pine)Forests in Al-Bayer and Al-Bassit Regions-Syria - Shater, Zuheir (Latakia University Journal -Biological Sciences Series, 2013)
This study was conducted in many natural sites in Al-Bayer and Al-Bassitregions inLattakiawhere there isthe main natural distribution of Brutia pine in Syria. The aim of the study is to analyse the relationship between the maincharacteristics of forest stands (forest mensuration) associated with silviculturetreatments, and plant diversity in the herbaceous layer of the forest. 32 circular plotsof 400 m2were sampled. Forest characteristics, plant species number and abundance(using Braun-Planquetindices)were recordedin each plot. Many diversity indices (SpeciesRichness, Shannon, Jaccard) were calculated. Species richness in the herbaceous layer correlated positively with age and negatively with volume, basal area, and forest cover in the over story. The effect of forest characteristics was more important on the vegetation composition than on the species richnessor Shannon index averages in the samples. Age was the most important characteristic influencing the vegetation composition, hence, the similarity between different age stages (expressed in Jaccard index). It is suggested in this study that when studying forest silviculture and management plans and when conserving biodiversity, life formsand functions must be considered instead ofthe traditional index.